Revisiting the Dynamics of the Fiscal Deficit and Inflation in India: the Nonlinear Autoregressive Distributed Lag Approach - Sharma, Vishal; Mittal, Ashok (Economy of Regions, 2021)
The chronic government deficit (fiscal deficit) and increase in the price level (inflation) have become major concerns for economists and policymakers. While numerous studies have examined the twin problems of the fiscal deficit and inflation for both developed and developing economies, their results are inconclusive due to different estimation techniques, chosen time periods, selection of variables, etc. Therefore, we examined the fiscal deficit-inflation nexus in India for the period from 1980-81 to 2016-17 by employing the Autoregressive Distributed Lag (ARDL) and Nonlinear Autoregressive Distributed Lag (NARDL) approaches. The results of the ARDL approach found no evidence of linear relationship between fiscal deficit and inflation in the Indian context. Further, the empirical findings of the NARDL model confirmed the nonlinear relationship between fiscal deficit and inflation in the long run and no association between money supply and inflation, supporting the ideas of the Fiscal Theory of the Price Level (FTPL) in the case of India. FTPL postulates that public debt and taxation policies drive price level; monetary policy has an indirect role only. Therefore, fiscal policymakers should focus on reducing fiscal deficits. Simultaneously, the Reserve Bank of India (RBI) should regulate lending interest rate so that a mix of fiscal and monetary policies can be applied for controlling inflation in India.